MODUS OPERANDI PELAKU ILLEGAL FISHING YANG BERDIMENSI TRANSNASIONAL DI INDONESIA - I Wayan Budha Yasa (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
This research was conducted with the aim to understand the transnational dimension of illegal fishing cases in Indonesia. This study aims to determine the modus operandi in cases of illegal fishing with a transnational dimension. This discussion is based on issues related to illegal fishing with a transnational dimension. This research is normative legal research by prioritizing a case approach. The data used in this study consisted of primary legal material and secondary legal material. The results of this study were analyzed qualitatively and presented descriptively. The results showed that the modus operandi used to carry out illegal fishing that can be known in the case of illegal fishing with a transnational dimension in this study, namely: (1) illegal fishing actors install ‘rumpon’ illegally in Indonesian fisheries management areas; (2) the perpetrator fishes in the Indonesian fisheries management area illegally or does not have a Fishing Business License and Fishing License from the Government of the Republic of Indonesia; and (3) perpetrators carry out illegal fishing by involving other actors who have their own roles. This can be seen from the presence of auxiliary vessels that support fishing efforts; (4) the perpetrator raised the flag of a country to deceive law enforcement officials; (5) vessels captained by perpetrators use trawl nets in fishing; and (6) use foreign skippers and crew.